Correlation between Emotional Intelligence and Tolerance in Students’ Communication (The Journal of Psychology and Sociology, 2018)
The article is devoted to the study of professionally significant qualities of the personality of students of the Kazakh National University named after al-Farabi. Features of emotional intelligence and communicative tolerance are examined, as well as their interrelation among students as important determinants of their future professional activity in modern conditions. Social problems of modern society associated with the growth of cruelty, violence, aggression, require greater attention of psychologists to the study and formation of personality traits, through which it is possible to counteract these phenomena. Personality tolerance and developed emotional intelligence are, in our view, precisely such qualities. The study of emotional intelligence, communicative tolerance and their interrelationship as factors that determine the success of professional activity in the field of "man-man" in modern conditions is, in our opinion, relevant. The article describes the methods used in the study, as well as the final results. A negative correlation was found between the integrative index of emotional intelligence and the overall indicator of communicative intolerance of the individual. The ways of formation of the considered personality qualities of students are proposed. Work to develop the emotional intelligence of students includes the formation of the following skills: arbitrarily manage their emotions, understand the emotions of others, develop empathy, build strong-willed qualities, etc. Work on the development of tolerance in communicating with others may include the formation of the following skills: accepting another person, adequately perceiving and evaluating oneself, expressing one's feelings when communicating with different people in a non-human form for another, attentively treating the characteristics of another person, perceiving the other as an individuality, respect the feelings of others, etc.Key words: professionally significant qualities of the personality; students of the pedagogical university; emotional intelligence; communicative tolerance; ways of forming.